2022
DOI: 10.1155/2022/8978878
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Factor Analysis for Predicting the Onset of Rotator Cuff Calcific Tendinitis Based on Artificial Intelligence

Abstract: Background. Symptomatic rotator cuff calcific tendinitis (RCCT) is a common shoulder disorder, and approaches combined with artificial intelligence greatly facilitate the development of clinical practice. Current scarce knowledge of the onset suggests that clinicians may need to explore this disease thoroughly. Methods. Clinical data were retrospectively collected from subjects diagnosed with RCCT at our institution within the period 2008 to 2020. A standardized questionnaire related to shoulder symptoms was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The most statistically significant values for prediction were the Jobe test, Bear hug test, and the age of the patients, with mean Shapley additive explanation (SHAP) values of 1.458, 0.950, and 0.790, respectively. Similarly, Dong et al [ 60 ] studied a cohort of 1967 patients through a human–computer interactive Electronic Medical System (EMS) and demonstrated the presence of predictors of RC calcific tendinitis stratified according to the patients’ sex: women diagnosed with diabetes mellitus and men diagnosed with hyperlipidemia, diabetes mellitus, and hypothyroidism showed a higher risk of developing RC calcific tendinitis. Clinical factors such as age and sex were investigated in both articles, similarly to this paper.…”
Section: Discussionmentioning
confidence: 99%
“…The most statistically significant values for prediction were the Jobe test, Bear hug test, and the age of the patients, with mean Shapley additive explanation (SHAP) values of 1.458, 0.950, and 0.790, respectively. Similarly, Dong et al [ 60 ] studied a cohort of 1967 patients through a human–computer interactive Electronic Medical System (EMS) and demonstrated the presence of predictors of RC calcific tendinitis stratified according to the patients’ sex: women diagnosed with diabetes mellitus and men diagnosed with hyperlipidemia, diabetes mellitus, and hypothyroidism showed a higher risk of developing RC calcific tendinitis. Clinical factors such as age and sex were investigated in both articles, similarly to this paper.…”
Section: Discussionmentioning
confidence: 99%
“…The literature reports a wide range of risk factors involved in the onset of calcific rotator cuff tendinitis, such as female sex, diabetes mellitus, dyslipidemia, hypothyroidism and other endocrine disorders [20], and in our experience a crucial role in the development of this condition is played by repetitive overhead movements and microtrauma, although individuals involved in strenuous manual labour or athletic activities are no more commonly affected than those leading sedentary lives. (Figure 2A,B) [21].…”
Section: Exposition Of the Theory Of The Formation And Dissolution Of...mentioning
confidence: 96%
“…AI technology offers promising advancements in predicting RCCT onset and facilitating targeted early-stage treatment. Dong et al [63] retrospectively analyzed clinical data from individuals diagnosed with RCCT at their institution. Logistic regression analysis revealed that female gender, hyperlipidemia, diabetes mellitus, and hypothyroidism were independent risk factors for symptomatic RCCT.…”
Section: Rotator Cuff Calcific Tendinopathy (Rcct)mentioning
confidence: 99%